2012
DOI: 10.1177/0963662512443407
|View full text |Cite
|
Sign up to set email alerts
|

Public Understanding of Science – a peer-review journal for turbulent times

Abstract: Scientific publications began as the exchange of polite letters among Gentlemen of Leisure interested in natural philosophy, during the period of the European Enlightenment in the 17th and 18th centuries. The 19th century saw the proliferation of national academies of sciences and societies for the advancement of science to the wider public. The formation of scientific disciplines was to follow, each with its own reviews for reporting new theories, observations and experiments to peers, and for critiquing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 1 publication
1
32
0
2
Order By: Relevance
“…From a historical point of view, several trends and observations have been described over the last few decades: First of all, the productivity of scholars in the field of science communication has increased significantly [e.g. Bauer and Howard, 2013;Borchelt, 2012]. The analysis by Trench and Bucchi [2015] of the geographic locations of the research contributions included in their anthology [Bucchi and Trench, 2014] reveal a positive trend in terms of both cross-institutional and cross-country collaborations -i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…From a historical point of view, several trends and observations have been described over the last few decades: First of all, the productivity of scholars in the field of science communication has increased significantly [e.g. Bauer and Howard, 2013;Borchelt, 2012]. The analysis by Trench and Bucchi [2015] of the geographic locations of the research contributions included in their anthology [Bucchi and Trench, 2014] reveal a positive trend in terms of both cross-institutional and cross-country collaborations -i.e.…”
mentioning
confidence: 99%
“…Irrespective of these trends, many scholars agree that scholars from Western, English-speaking countries continue to dominate the field [e.g. Bauer and Howard, 2013;Borchelt, 2012]. However, the bibliographic characteristics of science communication research outputs have rarely been analysed in a systematic way, despite the view that such overviews of research fields are important in identifying trends and challenges [Schäfer, 2012], or for defining a discipline [Gascoigne et al, 2010].…”
mentioning
confidence: 99%
“…Journals such as Social Studies of Science and Science, Technology, & Human Values have published a number of articles on science and publics in recent years. Moreover, the quantitative and survey-based research that predominated in early issues of Public Understanding of Science have given way to more methodologically varied and theoretically diverse contributions (Bauer and Howard, 2012). 8 The rousing sense of mission associated with that journal has waned somewhat and recent editorials have Between a Rock and a Hard Place 603 been rather less strident than those which featured in early issues (Bauer and Howard, 2012).…”
Section: Deficit and Diffusion Models In C21 Stsmentioning
confidence: 99%
“…Moreover, the quantitative and survey-based research that predominated in early issues of Public Understanding of Science have given way to more methodologically varied and theoretically diverse contributions (Bauer and Howard, 2012). 8 The rousing sense of mission associated with that journal has waned somewhat and recent editorials have Between a Rock and a Hard Place 603 been rather less strident than those which featured in early issues (Bauer and Howard, 2012). Meanwhile, influential studies have shown that science is being made in a variety of sites and by a diverse range of actors.…”
Section: Deficit and Diffusion Models In C21 Stsmentioning
confidence: 99%
“…Our own area of PCST studies was also studied reflexively with similar techniques, for example analyzing the production in one of the largest journals in the area -"Public Understanding of Science" [Bauer and Howard, 2012;Suerdem et al, 2013;Smallman, 2016].…”
Section: Computer-aided Analyses In Public Communication Of Science Amentioning
confidence: 99%